The Mediating Effect of Employee Loyalty on the Relationship Between Job Satisfaction and Organizational Performance - Zanabazar, Altanchimeg; Jigjiddorj, Sarantuya (SCAD Independent, 2021)
One of the key factors for sustaining an organizational performance for any organization is maintaining loyalty and retention of skilled and experienced employees. Therefore, revealing positive and negative factors impacting employee loyalty and taking action for further improvement has been an essential aspect for organizations. The current paper aims at researching how employee satisfaction has an impact on employee loyalty as well as the organizational performance of the organization based on the case of the Mongolian banks. The sample survey involved 400 employees of three banks. The results of the survey demonstrated that employee loyalty can be maintained through increasing employee satisfaction. In the present study employee satisfaction is considered as the independent variable and as mediating factor that served employee loyalty, and organizational performance is taken as the dependent variable. Consequently, reliability tests, correlation, and regression analysis have been carried out to prove our hypothesis. The research results indicate that satisfied employees tend to be loyal and committed to the organization and contributed positively to the organizational performance.